Enantio‐ and Diastereoselective Vinylogous Mukaiyama Aldol Reactions of α‐Keto Phosphonates with 2‐(Trimethylsilyloxy)‐ furan Catalyzed by Bis(oxazoline)‐Copper Complexes. Issue 2 (9th January 2013) - Hou, Gang; Yu, Jipan; Yu, Chengbin; Wu, Guiping; Miao, Zhiwei
Abstract The asymmetric vinylogous Mukaiyama aldol reaction between α‐keto phosphonate and 2‐(trimethylsilyloxy)furan was performed by using bis(oxazoline)‐copper complexes as the catalyst and 2, 2, 2‐trifluoroethanol as additive in dichloromethane. The present method is highly tolerable for functionalized α‐keto phosphonates and enabled us to obtain the corresponding 3‐ and 4‐substituted benzyl‐functionalized tertiary α‐hydroxy phosphonates in high yields (up to 86%) as well as high enantiostereoselectivities (up to 98% ee) and diastereoselectivities (up to 99:1, anti‐selective).